Simulations d’un modèle basé sur l’hypothèse du cycle de vie - Aubry, Jean-Pierre; Fleurent, Diane (L'Actualité économique)

(untitled) (HEC Montréal, 1979)
This study was undertaken in order to provide better insight into the dynamics of the life-cycle model and to develop a set of quantitative relationships that model the behaviour of macroeconomic aggregates. To begin, a microeconomic model was constructed which could, with a certain accuracy, reproduce behaviour patterns based on the life-cycle hypothesis and, with the aid of observed data on the Canadian population structure, generate a number of macroeconomic variables implied by this behaviour. The dynamics of this model were then examined in a number of simulations in which the effects of variations in population structure, as well as developments in incomes and the interest rate were analyzed. In a third step, we attempted to estimate certain standard consumption functions using the aggregate data generated by the model. While the estimates we obtained met current econometric criteria, these functions, especially where the interest rate was concerned, did not adequately reproduce the model used to generate the data. Finally we tested other formulations which seemed likely to yield a more acceptable representation of the basic model. This exercise, however, proved disappointing.In conclusion, it was ascertained that the study will have to be further refined in order to integrate into the macroeconomic formulations certain adjustments that would take into account demographic variations as well as the intertemporal substitution effect.